Legal Politics of Death Penalty Application in Indonesia - Suhendar Suhendar; Nur Rohim Yunus; Annissa Rezki (JOURNAL of LEGAL RESEARCH, 2022)
In Indonesia, the criminal law system is the one that decides the appropriate punishment for crimes and other legal transgressions. The use of the death sentence is still permitted under Indonesia's Criminal Code (KUHP), as well as some extra-criminal provisions. A translation of the Wetboek van Strafrecht voor Nederlandsch-Indie, which has been in effect in the Dutch East Indies (now known as Indonesia) since 1918 under the administration of the Dutch colonial government, can be found within the articles of the Criminal Code that govern the use of the death penalty. However, the Netherlands did away with the death sentence in 1870. Instead, a literature-based approach is used employing a qualitative research method currently being used. The study's findings indicate that significant crimes and the use of the death penalty throughout the history of criminal Law are two aspects of the problem that are strongly related. The legal system reserves the death penalty for those who have committed the most severe crimes. Therefore, many believe that the death penalty is the most severe punishment.